To be committed or not: a systematic review of the empirical literature on organizational commitment among correctional staff - Lambert, Eric G. (Criminal justice studies, 2021)
Staff are the most vital resource for any correctional facility. As corrections is a very expensive budget item in the U.S., finding and keeping dedicated employees is essential. Organizational commitment refers the bond between correctional staff and their institution. A strong bond is essential for the safety and security of both employees and inmates, as well as ensuring that the institution runs effectively. This review explores past research on three different types of organizational commitment (affective, moral, and continuance), in order to summarize past results and to reveal areas remaining unexplored. This paper examines both the antecedents and outcomes of organizational commitment. Through a systematic review of past studies, we have identified both positive and negative workplace factors that influence organizational commitment. In addition, we report how organizational commitment affects various outcomes, such as burnout and turnover intent. Understanding how to increase staff commitment can provide a blueprint for administrators to enhance correctional operations and employee satisfaction.